2021
DOI: 10.4018/ijdsgbt.294112
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for IT Governance Mechanisms in Uganda's Higher Institutions of Learning

Abstract: Poor implementation of Information Technology Governance (ITG) leads to several IT systems performing poorly. Resulting to discontinuity of services, user frustration, loss of IT investment, increased redundancy, duplication of efforts, poor decision-making, and reputation loss. In Uganda, implementation of ITG is low as many public sector organizations are yet to streamline. Yet, for Higher Institutions of Learning (HILs), the implementation of ITG is unexplored. Therefore, this study sought to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…First, the need to examine the relevance of the design artifact to the contextual environment upon evaluation and the key additions to knowledgebase shown by B and E. Second, the relevant knowledge from the knowledge base used to support the design and evaluation of the artifact in this study showed by D. The rigor cycle: this study adopted fundamental scientiðc approaches involving IT governance theories, IT governance frameworks, models and methodologies, and IT governance mechanisms to design. Which resulted in the development of a conceptual framework to implement IT governance in Uganda's HILs (Ndagire et al, 2021) as earlier mentioned. The evaluation was accomplished in two phases using case study and expert opinion methods.…”
Section: Application Of Design Science Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the need to examine the relevance of the design artifact to the contextual environment upon evaluation and the key additions to knowledgebase shown by B and E. Second, the relevant knowledge from the knowledge base used to support the design and evaluation of the artifact in this study showed by D. The rigor cycle: this study adopted fundamental scientiðc approaches involving IT governance theories, IT governance frameworks, models and methodologies, and IT governance mechanisms to design. Which resulted in the development of a conceptual framework to implement IT governance in Uganda's HILs (Ndagire et al, 2021) as earlier mentioned. The evaluation was accomplished in two phases using case study and expert opinion methods.…”
Section: Application Of Design Science Researchmentioning
confidence: 99%
“…The remaining constructs that were statistically significant (using a p-value of 0.05) were considered for the development of IGHU. Upon the establishment of the conceptual framework to implement IT governance in Uganda's HILs (Ndagire et al, 2021), a framework evaluation was carried out. The internal environment mechanisms were: IT strategy committee, CIO reporting to CEO, architecture steering committee, accountability of IT projects, IT risk management, IT leadership, IT/business partnership, senior management involvement, and awareness campaigns.…”
Section: Development Phasementioning
confidence: 99%